Evaluating the Skin Interactions and Permeation of Alginate/Fucoidan Hydrogels Per Se and Associated with Different Essential Oils - Ana Isabel Barbosa; Sofia A. Costa Lima; Ibraheem Yousef; Salette Reis (MDPI AG, 2023)
Marine polysaccharides are recognized for their biological properties and their application in the drug delivery field, favoring hydrogel-forming capacities for cutaneous application towards several dermatological conditions. Essential oils have been widely used in skin, not only for their remarkable biological properties, but also for their capacity to enhance permeation through the skin layers and to confer a pleasant scent to the formulation. In this study, menthol, L-linalool, bergamot oil, and β-pinene were incorporated in alginate/fucoidan hydrogels to evaluate their skin permeation enhancement profile and assess their influence on the skin organization. The combinations of different essential oils with the marine-based fucoidan/alginate hydrogel matrix were characterized, resulting in formulations with pseudoplastic rheological properties favorable for a uniform application in the skin. The ex vivo Franz diffusion permeation assays revealed that calcein loaded in bergamot-alginate/fucoidan hydrogel permeated more than 15 mg out of the initial 75 mg than when in linalool-alginate/fucoidan, alginate/fucoidan or hydrogel without any incorporated oil. Skin calcein retention for menthol- and pinene-alginate/fucoidan hydrogels was 15% higher than in the other conditions. Infrared micro-spectroscopic analysis through synchrotron-based Fourier Transform Infrared Microspectroscopy evidenced a symmetric shift in CH3 groups towards higher wavenumber, indicating lipids' fluidization and less lateral packing, characterized by a band at 1468 cm−1, with the bergamot-alginate/fucoidan, which contributes to enhancing skin permeation. The study highlights the effect of the composition in the design of formulations for topical or transdermal delivery systems.